Combating antibiotic resistance using guidelines and enhanced stewardship in Kenya: a protocol for an implementation science approach. Issue 3 (31st March 2020) - Gitaka, Jesse; Kamita, Moses; Mureithi, Dominic; Ndegwa, Davies; Masika, Moses; Omuse, Geoffrey; Ngari, Moses; Makokha, Francis; Mwaura, Peter; Mathai, Ronald; Muregi, Francis; Mwau, Matilu
Abstract : Introduction: Antimicrobial resistance (AMR) is a growing problem globally especially in Sub-Saharan Africa including Kenya. Without any intervention, lower/middle-income countries (LMICs) will be most affected due to already higher AMR levels compared with higher income countries and due to the far higher burden of diseases in the LMICs. Studies have consistently shown that inappropriate use of antimicrobials is the major driver of AMR. To address this challenge, hospitals are now implementing antibiotic stewardship programmes (ASPs), which have been shown to achieve reduced antibiotic usage, to decrease the prevalence of resistance and lead to significant economic benefits. However, the implementation of the guideline is highly dependent on the settings in which they are rolled out. This study, employing an implementation science approach, aims to address the knowledge gap in this area and provide critical data as well as practical experiences when using antibiotic guidelines and stewardship programmes in the public health sector. This will provide evidence of ASP performance and potentially contribute to the county, national and regional policies on antibiotics use. Methods and analysis: The study will be conducted in three geographically diverse regions, each represented by two hospitals. A baseline study on antibiotic usage, resistance and de-escalation, duration of hospital stay, rates of readmission and costs will be carried out in the preimplementation phase. The intervention, that is, the use of antibiotic guidelines and ASPs will be instituted for 18 months using a stepwise implementation strategy that will facilitate learning and continuous improvement of stewardship activities and updating of guidelines to reflect the evolving antibiotic needs. Ethics and dissemination: Approvals to carry out the study have been obtained from the National Commission for Science, Technology and Innovation and the Mount Kenya University Ethics Review Committee. The approvals from the two institutions were used to obtain permission to conduct the study at each of the participating hospitals. Study findings will be presented to policy stakeholders and published in peer-reviewed scientific journals. It is anticipated that the findings will inform the appropriate antibiotic use guidelines within our local context.